2015
DOI: 10.3109/09553002.2015.997895
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of radiation-induced H2AX phosphorylation on histone methylation: Evidence from the chromatin immunoprecipitation assay

Abstract: These data strengthen the dependence of IR-induced DNA damage response on the chromatin region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The packaging degree of the DNA has consequences for the repair process. This is especially true for the densely packed heterochromatin because the damaged DNA has to be histone free for the repair and must also be accessible for the repair protein complexes [46,47,48]. It has been shown that DSBs in the heterochromatin region are usually be repaired at the border of heterochromatic chromatin regions [1,2,14,49] whereby the methylation degree typical for heterochromatin remains unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…The packaging degree of the DNA has consequences for the repair process. This is especially true for the densely packed heterochromatin because the damaged DNA has to be histone free for the repair and must also be accessible for the repair protein complexes [46,47,48]. It has been shown that DSBs in the heterochromatin region are usually be repaired at the border of heterochromatic chromatin regions [1,2,14,49] whereby the methylation degree typical for heterochromatin remains unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…In mice, radiation exposure led to decreased trimethylation of histone H4 lysine which might result in relaxed heterochromatin organisation and would impair genome stability [26] . It has been shown in human cells that euchromatic regions were more susceptible to radiation-induced DNA damage and γH2AX accumulation [58][59][60] .…”
Section: Chromatin Remodelling and Radiationmentioning
confidence: 99%
“…Accumulations of the oxidative stresses and persistent pro-inflammatory responses cooperatively alters the cellular and mitochondrial redox balance, forms oxidized nucleotides, and impairs the DNA repair capacity, which results in DNA damages ( Dąbrowska and Wiczkowski, 2017 ; Czarny et al, 2018 ; Moloney and Cotter, 2018 ). Previous studies showed that genes in euchromatic regions were more susceptible to both HDR‐ and LDR-induced DNA damage, double-strand break, and r-H2AX accumulation ( Puck et al, 2002 ; Lafon-Hughes et al, 2008 ; Sak et al, 2015 ). Therefore, LDR-induced stresses convergently led to the permanent changes in the cells.…”
Section: Introductionmentioning
confidence: 99%